Pemanfaatan Citra Sentinel 2A Untuk Pemetaan Sebaran Ekosistem Lamun Di Perairan Pulau Panjang, Bangka Tengah - Salmia Septiani; Irma Akhrianti; Aditya Pamungkas (Universitas Bangka Belitung, 2022)
Remote sensing techniques by utilizing satellite imagery can provide many advantagesin assessing information about the distribution of seagrass ecosystem in the Panjang Island waters. By using Sentinel 2A satellite imagery with a spatial resolution of 10 m, this study will provide information about the condition of seagrass beds in Panjang Island. The next step is the application of the Depth Invariant Index (DII) algorithm or the water column correction with the Lyzenga algorithm on the image. Based on the results of the supervised classification in ENVI 5.2 software, the color hue of each class shows a different color. There are six classes, namely land, seagrass, rubble / coral fragments, reef coral, sand and sea. The area of seagrass has an area of about 70.24 ha. There are 7 types of seagrass found in the waters of Panjang Island. Among them are, Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halophila ovalis, Halodule uninervis, Syringodium isoetifolium, and Halodule pinifolia. The percentage of seagrass cover based on the results of the field survey has an average of 9.84% which is categorized as poor/damaged. The lowest percentage with a value of 3.48% is at station 3 and the highest with a value of 12.91% is at station 2.